CARDIOPULMONARY DEATHS IN BRASIL AND IN THE VALE DO SÃO PATRÍCIO (CIPEEX, 2025)
Cardiopulmonary diseases remain one of the leading causes of mortality in Brazil, significantly affecting the population’s quality of life and overburdening public health services. In the regional context, the analysis of these causes of death allows for a deeper understanding of local impacts and the need for preventive strategies. The objective was to analyze deaths caused by cardiopulmonary diseases in Brazil and in the municipalities of Nova Glória and Itapaci in the years 2023 and 2024, during the same period. This is a descriptive study based on secondary data provided by official health records in Brazil, as well as those of the municipalities of Nova Glória and Itapaci. Deaths occurring in 2023 and 2024 were considered. In Brazil, there is an estimate of 200,000 cardiopulmonary arrests annually, with 100,000 occurring in out-of-hospital settings and 100,000 in hospital environments. Statistical data show that smoking is responsible for 37,686 deaths related to COPD. In the municipality of Nova Glória, deaths from cardiopulmonary diseases increased from 18 in 2023 to 25 in 2024, representing a significant rise that may indicate worsening health conditions in the local population. In the municipality of Itapaci, a total of 239 deaths from cardiopulmonary diseases were recorded between 2023 and 2024, demonstrating the relevance of the problem in the region. These data reinforce the need for public policies aimed at prevention and early treatment of these conditions. The data analyzed in Brazil show a high number of deaths from cardiopulmonary diseases, as well as in the municipalities of Nova Glória and Itapaci. Such information highlights the importance of strategic health actions focused on prevention, early diagnosis, and continuous care for at-risk patients, in order to reduce mortality from these conditions in the region.
Keywords: Cardiopulmonary Diseases1; Deaths2; Brazil3; Public Health4; Nova Glória5; Itapaci6